2016 IEEE International Conference on Robotics and Automation (ICRA) 2016
DOI: 10.1109/icra.2016.7487525
|View full text |Cite
|
Sign up to set email alerts
|

Real-time, GPU-based pose estimation of a UAV for autonomous takeoff and landing

Abstract: This paper proposes a real-time system for pose estimation of an Unmanned Aerial Vehicle (UAV) using parallel image processing of a known marker. The system exploits the capabilities of a high-performance CPU/GPU embedded system in order to provide on-board high-frequency pose estimation, eliminating the need for transmitting the video stream offboard, and enabling autonomous takeoff and landing. The system is evaluated extensively with lab and field tests on board a small quadrotor. The results show that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 17 publications
0
14
0
1
Order By: Relevance
“…Zhuang et al [12] used the line features of the airport and the monocular camera on board to provide pose information for UAV autonomous landing. Benini et al [13] estimated the pose of a UAV by detecting a marker composed of known circles for autonomous takeoff and landing. For scenes without known landmarks, the structure from motion (SFM) [14,15,16] method or the simultaneous localization and mapping (SLAM) [17,18] method can be leveraged to estimate the relative pose for aircraft navigation.…”
Section: Introductionmentioning
confidence: 99%
“…Zhuang et al [12] used the line features of the airport and the monocular camera on board to provide pose information for UAV autonomous landing. Benini et al [13] estimated the pose of a UAV by detecting a marker composed of known circles for autonomous takeoff and landing. For scenes without known landmarks, the structure from motion (SFM) [14,15,16] method or the simultaneous localization and mapping (SLAM) [17,18] method can be leveraged to estimate the relative pose for aircraft navigation.…”
Section: Introductionmentioning
confidence: 99%
“…Known 3D geometry features in observed scenes are exploited and a perspective-and-point (PnP) algorithm is selected to estimate the pose accurately. Benini et al [44] proposed an aircraft pose estimation system based on the detection of a known marker. The on-board system performs high-frequency pose estimation for autonomous landing using parallel image processing.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the algorithm in [13] is limited to human pose estimation, applicable for lowresolution images and has longer execution time than our implementation. The algorithm described in [14] is used for highly accurate pose estimation in un-manned air vehicles (UAV) for takeoff and landings. The authors in [14] perform a field evaluation using low end GPUs such as Jetson TK1.…”
Section: Introductionmentioning
confidence: 99%
“…The algorithm described in [14] is used for highly accurate pose estimation in un-manned air vehicles (UAV) for takeoff and landings. The authors in [14] perform a field evaluation using low end GPUs such as Jetson TK1. It is observed that pose estimation takes under 25 milliseconds for standard 640 × 480 images.…”
Section: Introductionmentioning
confidence: 99%